Evaluation of the effects of increasing doses of meloxicam on hematological, biochemical and hemostatic blood parameters in sheep - Fulya Altınok Yipel; Hüseyin Güngör (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the study was to determine the effect of intravenous administration of meloxicam at increasing doses (0.5, 1 and 2 mg/kg) on hematological, biochemical and coagulation parameters in sheep. Materials and Methods: Clinically healthy sheep were randomly divided into groups as Group 1 (n:6), Group 2 (n:6) and Group 3 (n:6). Meloxicam was administered intravenously as a single dose of 0,5 mg/kg in Group 1, 1 mg/kg in Group 2 and 2 mg/kg in Group 3. To determine the effect of increasing single doses of meloxicam on hematological, biochemical and coagulation factors, blood samples were collected at 0, 24, and 72 hours. In addition, hemogram (RBC, MCV, MCH, MCHC, HCT, WBC, HGB, RDW, MPV, PDW, PCT, PLT) and biochemical parameters (AST, ALT, ALP, GGT, TP, UREA, CREA, CHOL, TRIG, ALB) ) and the levels of coagulation parameters (PT, APTT, INR, FIB) were determined. Results: In groups; Differences in biochemical parameters other than UREA and parameters of RBC, HCT, MCV, MCHC, MPV were statistically significant (p<0,05). It was observed that there was no statistically significant difference in terms of their relationship with hemostatic blood parameter levels. Conclusion: In conclusion, it is thought that further studies techniques such as molecular diagnostic methods are needed in terms of hemostatic, hematological and biochemical effects of increasing single doses of meloxicam in sheep.